Growth pattern and control of Dieffenbachia seguine (Jacq.) Schott - Sharifah Mariam S.M.,; Ipor I.B.,; Mohd Hazwan Fikri A.R., (Penerbit Universiti Kebangsaan Malaysia, 2017)
Dieffenbachia seguine (Jacq.) Schott (Araceae) is an herbaceous perennial plant. It was introduced in Malaysia as an ornamental plant. This present study is mainly to determine the growth pattern, biomass allocation and chemical control of D. seguine in oil palm area at Kampung Terasi, Sadong Jaya, Kota Samarahan, Sarawak. Five quadrates of 1m x 1m were established in both area, open and shaded areas in 4 years old oil palm plantation. The highest total number of plants and leaves were recorded at the open area. While shaded areas have the highest value for the leaf area (LA), the specific leaf area (SLA) and the leaf area ratio (LAR). The plant parts that contribute to the highest biomass partitioned are, the roots and stems at the opened areas and the leaves and petioles for shaded areas. The highest sprouting of D. seguine via stem cutting was recorded during the immature growth stage and when the plant has three nodes. Six treatment were done to control this plant, however it does not show 100% desiccation effects. The three single treatments are, 2,4-D dimethylamine, metsulfuron methyl and paraquat dichloride and the three combination treatments are, 2,4-D dimethylamine and metsulfuron methyl, paraquat dichloride and metsulfuron methyl and lastly metsulfuron methyl and glyphosate-isopropylammonium. The most effective method to control the growth of D. seguine is the combination of 2,4-D dimethylamine and metsulfuron methyl.